DEVELOPMENT OF THE MASS AND QUANTITY WHEEL MEDIA TO FACILITATE CONCRETE MATHEMATICS LEARNING - Abdur Rohim; Orchie Adellia Suci Rahmadhinie (LPPM Universitas Islam Darul `Ulum Lamongan, 2026)
This study aimed to develop and examine the feasibility of the Mass and Quantity Wheel (ROMAKU) as a mathematics learning medium for elementary school students. The research employed a Research and Development (R&D) approach using the ADDIE model, which consists of analysis, design, development, implementation, and evaluation stages. The trial was conducted with 10 fourth-grade students at SD Negeri 3 Pandanpancur. Data were collected through observation, interviews, questionnaires, and pre-test and post-test assessments. Media validity was analyzed using Aiken’s V, practicality was measured through student response questionnaires, and effectiveness was analyzed using the N-Gain method. The results showed that the ROMAKU learning media achieved a validity score of 0.82 categorized as very valid, a practicality score of 0.80 categorized as practical, and an effectiveness score with an N-Gain value of 0.64 in the moderate category. These findings indicate an improvement in students’ understanding of mass units and quantity concepts after using the ROMAKU media. Therefore, the ROMAKU media is considered feasible as an alternative concrete, manipulative, and interactive mathematics learning medium to support meaningful learning in elementary schools.